Mobile-Assisted Task-Based Language Learning, Writing Competency, And Motivation - Adelina Kartika Dewi; Ni Made Ratminingsih; Made Hery Santosa (Jurnal Pendidikan Indonesia, 2020)
This quasi-experimental study aimed at investigating the effect of mobile-assisted task-based learning on students’ writing competency and students’ motivation in writing. Post-test only control group design was employed in this study. The experimental group was taught by mobile-assisted task-based learning while the control group was taught by non mobile-assisted task-based learning. A writing post-test and questionnaire were used to obtain the data and were analyzed using one-way ANOVA and MANOVA. The findings of the study revealed that (1) there was a significant effect of Mobile-assisted Task-based Learning on the students’ writing competency; (2) there was a significant effect of Mobile-assisted Task-based Learning on the students’ writing motivation; and (3) there was a simultaneous effect of Mobile-assisted Task-based Learning on the students’ writing competency and students’ motivation in writing. This study concluded that the use of mobile devices as a medium in the learning process is effective to enhance the students’ writing competency and increase students’ motivation in writing.